Nonlinear assessment of motor variability during practice and competition for individuals with different motivational orientations. - Studenka, Breanna E.; Dorsch, Travis E.; Ferguson, Natalie L.; Olsen, Cameron S.; Gordin, Richard D. (Learning & Motivation, 2017)
The aim of the present study was to document how differing motivational orientation profiles, situated within environmental constraints (i.e., a competitive and practice environments) influence the nonlinear variability of performance and subsequent retention of a visual motor tracking skill. Myriad research associates atypical nonlinear aspects of motor variability with pathology; however, few empirical efforts have explored the influence of individual differences and environmental factors on nonlinear aspects of motor output and skill retention. Participants performed an isometric force-tracking task, matching the force indicated by a target line displayed across a computer screen. Dependent variables were performance outcome (root mean squared error) and the complexity of the produced signal (Sample Entropy) across practice, competition, and retention. Participants with high task orientation, regardless of high or low levels of ego orientation, exhibited the greatest visual motor tracking improvement as well as the greatest increases in irregularity of force variability from practice to competition and retention. We conclude that individual differences play a key role in the structure of continuous behavior, and that this structure influences the learning of continuous motor skills.